EMPING MELINJO BUSINESS DEVELOPMENT STRATEGY (CASE STUDY: IN ALUR GADUNG VILLAGE, PADANG TUALANG DISTRICT, LANGKAT REGENCY) - As'ad, Octasella Ainani; Yanti, Mariana Eva; Nasution, Nurhadida; Surbakti, Supriadi (Institute of Computer Science (IOCS), 2024)
The emping melinjo business has been running for quite a long time. However, the people in Alur Gadung Village are experiencing difficulties in developing their emping melinjo business, especially in marketing. Apart from that, there is also the problem of limited capital and production or it is difficult to find old melinjo seeds, because melinjo seeds bear fruit depending on the season, they are not always available in the area. Emping Melinjo business in Alur Gadung Village, District. Padang Tualang District. Langkat Therefore, Emping Melinjo emping entrepreneurs must have a good and reliable marketing strategy, so that their products not only sell well in the market, but are able to compete and will last a long time in the existing competitive world. The Emping Melinjo Business Enterprise is expected to truly be able to know all forms of product strengths and weaknesses in the internal conditions of the Emping Melinjo business, so that it is able to manage conditions well in terms of production.